Establishing and Maintaining an Extensive Library of Patient-Derived Xenograft Models - Mattar, Marissa; McCarthy, Craig R.; Kulick, Amanda R.; Qeriqi, Besnik; Guzman, Sean; de Stanchina, Elisa (Frontiers in Oncology, 2018)
Patient Derived Xenograft (PDX) models have recently emerged as a highly desirable platform in oncology and are expected to substantially broaden the way in vivo studies are designed and executed and to reshape drug discovery programs. However, acquisition of patient derived samples, and propagation, annotation and distribution of PDXs are complex processes that require a high degree of coordination among clinic, surgery and laboratory personnel, and are fraught with challenges that are administrative, procedural and technical. Here we examine in detail the major aspects of this complex process, and relate our experience in establishing a PDX Core Laboratory within a large academic institution.